2021
DOI: 10.1136/bmjgh-2021-006760
|View full text |Cite
|
Sign up to set email alerts
|

Integrating community-based verbal autopsy into civil registration and vital statistics: lessons learnt from five countries

Abstract: This paper describes the lessons from scaling up a verbal autopsy (VA) intervention to improve data about causes of death according to a nine-domain framework: governance, design, operations, human resources, financing, infrastructure, logistics, information technologies and data quality assurance. We use experiences from China, Myanmar, Papua New Guinea, Philippines and Solomon Islands to explore how VA has been successfully implemented in different contexts, to guide other countries in their VA implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“… 25 Our finding of favorable agreement scores, the minimal proportion of undermined deaths, and low disagreement rate between the 2 interviewers indicate SmartVA can generate high-quality verbal autopsy data in rural settings and has the potential to be used as a tool for medical certification of deaths in community settings. 26 These findings have implications for improving the quality of death reporting from rural communities which is vital for developing meaningful policies.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Our finding of favorable agreement scores, the minimal proportion of undermined deaths, and low disagreement rate between the 2 interviewers indicate SmartVA can generate high-quality verbal autopsy data in rural settings and has the potential to be used as a tool for medical certification of deaths in community settings. 26 These findings have implications for improving the quality of death reporting from rural communities which is vital for developing meaningful policies.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies reported on CBIS implementations (n=78) in Africa, including Ethiopia, 16 – 23 Malawi, 24 – 32 Kenya, 31 , 33 – 36 Uganda, 37 – 42 South Africa, 8 , 43 46 Mali, 47 50 among others. 6 , 7 , 39 , 51 – 80 Twenty-six CBIS implementations were reported in Asia, including India, 81 86 Bangladesh, 10 , 87 89 Papua New Guinea, 9 , 10 , 87 , 90 Cambodia, 91 – 93 Myanmar, 87 , 94 , 95 among others. 96 – 100 , 103 Only 1 CBIS implementation was reported in South America: Colombia.…”
Section: Resultsmentioning
confidence: 99%
“…However, common examples of CBISs include community monitoring systems for maternal, newborn, and child health (MNCH) and PHC services, commodities and stock management (e.g., medication volumes and supplies) at the community level, disease-specific surveillance (e.g., malaria), or collection of community data for civil registration and vital statistics (CRVS) systems. 9 , 10 CBISs differ from traditional health information systems (HISs) in that the primary data collection is performed at the community level, typically as part of a health service encounter, and reported to health facilities in an aggregate format. CBISs can be used to identify populations in need, address challenges with access and accountability, and improve equity.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that the implementation of improved death registration practices and routine application of automated VA in Myanmar can yield plausible and critical information on the causes of community deaths in the country. Myanmar showed significant progress in implementing and institutionalising improved death reporting and VA practices at scale between 2016–2020 [ 21 ]. The findings suggest that improving completeness of VA reporting in poorly performing townships, as well as among women, is needed to improve the policy utility, and generalisability, of these results.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation workshops were conducted in townships and provided an opportunity to provide feedback to these frontline workers, address their challenges and concerns and coach them on how to deliver the VA intervention more effectively. Further information on engagement with VA interviewers, training and supervisory activities can be found elsewhere [ 21 ].…”
Section: Methodsmentioning
confidence: 99%